Instalaciones eléctricas y consumo energético en el taller metalmecánico cm de la ciudad de Ambato en el año 2017.propuesta de un plan alternativo de optimización energética - Chiluisa cueva, Carlos fernando (2018)
This research was carried out in the workshop Metalmecánico CM was located in the city of Ambato, where it was identified that in this workshop the energy consumption is excessive and that there is no energy studies, nor the audit programs that guarantee the energy efficiency of the workshop. The present project has the purpose of designing a plan of energy optimization of the model for the management of the electrical consumption and of the electrical energy that applies the model of management of energy ISO 50001, for the electrical analysis with the national regulation CONELEC 004/01 that indicate the limits that must be met to improve the quality of electric power.For the development of the theme, an energy quality meter was installed, which was connected to the output of the main board of the workshop, obtaining measurements every 15 minutes in a period of seven days as established by the standard. With the analysis of these measurements and the help of the EASY POWER technical software, results were obtained that show a low power factor and the presence of currentharmonics that cause the deterioration in the useful life of the company's equipment. When finding the problems present in the company, alternative solutions were proposed to reduce the penalization costs due to low power factor that the Electricity Company of Ambato EEASA charges to this industry monthly, as well as to reduce the levels of harmonic contamination that are produced by the use of non-linear loads.